Application of a molecular diagnostic algorithm for haemophilia A and B using next-generation sequencing of entire F8, F9 and VWF genes - Bastida, Jose Maria; González-Porras, Jose Ramon; Jiménez, Cristina; Benito, Rocio; Ordoñez, Gonzalo R.; Álvarez-Román, Maria Teresa; Fontecha, M. Elena; Janusz, Kamila; Castillo, David; Fisac, Rosa Maria; García-Frade, Luis Javier; Aguilar, Carlos; Martínez, Paz Maria; Bermejo, Nuria; Herrero, Sonia; Balanzategui, Ana; Martin-Antorán, Jose Manuel; Ramos, Rafael; Cebeiro, Maria Jose; Pardal, Emilia; Aguilera, Carmen; Pérez-Gutierrez, Belen; Prieto, Manuel; Riesco, Susana; Mendoza, Maria Carmen; Benito, Ana; Benito-Sendin, Ana Hortal; Jimenez-Yuste, Victor; Hernández-Rivas, Jesus Maria; García-Sanz, Ramon; González-Díaz, Marcos; Sarasquete, Maria Eugenia (Thrombosis and Haemostasis, 2017)
Currently, molecular diagnosis of haemophilia A and B (HA and HB) highlights the excess risk-inhibitor development associated with specific mutations, and enables carrier testing of female relatives and prenatal or preimplantation genetic diagnosis. Molecular testing for HA also helps distinguish it from von Willebrand disease (VWD). Next-generation sequencing (NGS) allows simultaneous investigation of several complete genes, even though they may span very extensive regions. This study aimed to evaluate the usefulness of a molecular algorithm employing an NGS approach for sequencing the complete F8, F9 and VWF genes. The proposed algorithm includes the detection of inversions of introns 1 and 22, an NGS custom panel (the entire F8, F9 and VWF genes), and multiplex ligation-dependent probe amplification (MLPA) analysis. A total of 102 samples (97 FVIII- and FIX-deficient patients, and five female carriers) were studied. IVS-22 screening identified 11 out of 20 severe HA patients and one female carrier. IVS-1 analysis did not reveal any alterations. The NGS approach gave positive results in 88 cases, allowing the differential diagnosis of mild/moderate HA and VWD in eight cases. MLPA confirmed one large exon deletion. Only one case did have no pathogenic variants. The proposed algorithm had an overall success rate of 99 %. In conclusion, our evaluation demonstrates that this algorithm can reliably identify pathogenic variants and diagnose patients with HA, HB or VWD.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Haemophilia A; haemophilia B; von Willebrand disease; molecular diagnosis; next-generation sequencing